Exploring consumers' experiences in electronic word-of-mouth for health supplement purchases - Nasiruddin, Kauthar (2022)
Electronic word of mouth which is disseminated via Internet plays a vital role in substituting the power of advertisement. There are approximately 24.5 million of Internet and social media users in Malaysia. The enormous number of social media users makes it more apparent that social media has become a valuable platform to promote products and services. Extensive use of social media made people easily exposed to other users’ daily activities, lifestyle as well as sharing of opinions and experience. Hence, the level of awareness on health and beauty among consumers in Malaysia becomes more prevalent. There is a variety of health and dietary supplements available in the market. Among Asian countries, obesity and overweight rate are the highest in Malaysia with 64% of male and 65% of female population being either obese or overweight, ranked sixth in the Asia Pacific region as well as the top country within Southeast Asia for both obesity and diabetes (World Health Organization, 2019). Rapid urbanization in Malaysia resulting in rapid changes of dietary intakes including weight management supplement intakes. Information pertaining to weight management supplements have been extensively spread via social media. The supplement industry in Malaysia has been growing rapidly recently due to a paradigm shift in healthcare management and some factors were found to be influential to the purchase intention of these health supplements (Yeo et. al, 2022). The availability and sales of the weight management supplements in the market is increasing but the issue with obesity and overweight is still rising (Ghazali, et al, 2006). Hence the researcher wonders on the sources that influence consumers to trust the information disseminated via electronic word of mouth and purchased these health supplements. Social media has become a good platform of electronic word of mouth to advertise products and services since consumers trust information shared randomly by people more than advertisements (Bao and Chang, 2014). Thus, it is believed to be a great platform as behavioural change agent which affects consumers’ reactions to products or services as well as creating opportunities to marketers (Kranzler, & Beakley, 2019). The purpose of this research was to explore the experience of weight management supplement consumers in trusting electronic word of mouth which made them decided to purchase. It also aimed to understand the process of how consumers made their decision before purchasing. This study was carried out through an in-depth exploration of some research questions. The questions were 1) What are the factors that influence consumers to trust the electronic word of mouth in the purchase of weight management supplements? 2) What sort of information on social media that influence consumers to trust the product? In-depth interviews were essential in obtaining the experience of the consumers on this. This study involved a qualitative research methodology which applied descriptive phenomenology approach. Data was gathered from seven weight management supplement consumers who have volunteered to be interviewed. The data was obtained using in depth interview. The interview session lasted for around 30-90 minutes, was audio recorded, transcribed verbatim and analysed using a hands-on approach. Some other documents have also been used such as resources from the library, journals and logs. The trustworthiness of this research was done through members checking. The findings reveal that electronic word of mouth plays as behaviour change agent. Emotion, personality, perception, culture, reference group, motivation and learning affects the level of trust among consumers. For future research, it is recommended that similar study could be expanded to another qualitative inquiry to gain comprehensive observation.